Organizational principles of knowledge in a nursing program - Alix Yaneth Perdomo Romero; Claudia Andrea Ramírez Perdomo; Dolly Arias Torres (Universidad de Costa Rica, 2014)
This article presents the results of a study aimed at describing the organizational principles of knowledge in the training of professionals nursing surcolombianos. The study is qualitative and quantitative, cross- sectional and descriptive. The population was composed of 20 teachers and 80 students. Data collection was conducted through survey and semi-structured interview. The results demonstrate that the curricular structure of the Nursing Program is to discipline, academic, predominantly an asignaturista model with ranking courses, content duplication, and fragmented work gap between theory and practice. No integration axes are detected, nor interdisciplinarity. We conclude they must overcome the discipline prototype and continuity of the asignaturista traditional curriculum. The Interdisciplinary curriculum ensures that the strengths of the curriculum make an enhance and integrate theoretical framework and methodological to avoid the fragmentation of knowledge.